Two essays assessing the agribusiness labor market - Castro, Nicole Rennó (2018)
Changes caused by globalization and internationalization in recent decades have stimulated the modernization of the agriculture and strengthened the interdependence between primary (farm) production and upstream and downstream activities, consolidating the so-called \"agribusiness\". This closer relationship between the links of the agribusiness chain connects the dynamics of the labor market in its segments. However, despite the importance of agribusiness to the Brazilian economy and society and the interrelationship between the labor markets of its segments, there is no employment evaluation approach that considers agribusiness as a whole in Brazil. Studies that analyze the labor market in this sector are also scarce in the literature, technical or scientific. This thesis sought to make a first contribution towards filling this gap. In the first chapter, where we also created the basis for the second, we provide a new approach that allows to measure the Brazilian agribusiness labor market considered as a whole. Additionally, as empirical exercises, we analyzed some additional characteristics of the sector labor force and the effects of some employment-related income determinants on income differences among agribusiness workers. Our main database was the 2014 quarterly microdata of the Pesquisa Nacional por Amostra de Domicílios Contínua (PNAD-C [Continuous National Household Sample Survey]). We also used information from the Relação Annual de Informações Sociais (RAIS [Annual Social Information Report]) and Cepea calculations. Our main findings are: 19 million people, 21% of the country\'s workforce, worked in the Brazilian agribusiness sector in 2014; agribusiness workers were predominately unskilled or semi-skilled with little formal education; much of the sector workforce was not formally employed; and there is an extreme labor market heterogeneity among agribusiness sector segments - with the primary segment presenting a noticeably dissimilar profile - and a significant income differential associated with different employment statuses and job market locations. In the second chapter, we analyze the significant increase in employment-related income in agribusiness based on labor productivity, real unit labor cost and the relationship between the GDP sector deflator and the IPCA, between the years 2004 and 2015. For that, we apply the procedure that Barros (2016) developed to analyze this issue for the Brazilian economy as a whole. To find the total number of employees in agribusiness (and sub-segments) in the analyzed period and to calculate labor productivity in the sector, we implemented an adaptation of the methodology developed in the first chapter of the thesis. As main results, we found that in agribusiness, there was no preponderant role of the relationship between the sector deflators and the IPCA to mitigate the effects of employment-related income growth on labor cost to the employer, as occurred in Brazil as a whole. Nevertheless, real labor income gains practically did not influence labor costs, mainly due to productivity gains in the sector, boosted by its primary segment. Without this productivity growth, real labor costs to the employer would increase at the annual rate of 3.4%, adversely affecting or even rendering unfeasible the simultaneous gains of agribusiness employers and workers in the period.